Research on Development Strategy of Henan Aviation Economy under the Background of Regional Economy. (11th July 2022) - Yu, Guo; Hao, Aimin; Liu, Chunling
Abstract : There is no doubt that economic globalization creates a golden opportunity for the development of aviation economy in the world; meanwhile, the world economy has entered the aviation century of the 21st century from the navigation century of the 20th century. As a new type of regional economy, the aviation economy is attracting more and more attention from all sectors of society and becoming a significant field for many countries and regions in the world. As the city that has been strategically promoted as the first pilot zone for airport economy development in China (Liang, 2013), Zhengzhou is endowed with remarkable geographic advantage. Coupled with policy advantages from Chinese government, its development is crucial to the development of regional economy in the entire province; therefore, this research paper studied its advantages, disadvantages, opportunities, and threats for developing aviation economy and analyzed its possibility for developing a well-established aviation industry. Secondly, the current condition of airport logistics in Henan province was analyzed, especially the current situation and noticeable problems. Thirdly, the gray analysis was carried out to analyze the relationship between aviation industry and economy development in Henan. Finally, the according development strategy and suggestions for developing aviation economy were put forward, such as innovating industrial development models, exploring new modes of financing, establishing a sound transportation system and airport supporting facilities, and improving the talent introduction program in airport industry. Overall, this paper researched the aviation economy in Henan province from the perspective of regional economy development, analyzed the current issues occurred in the aviation economy development process, and offered suggestions accordingly.